2012
DOI: 10.1371/journal.pone.0046908
|View full text |Cite
|
Sign up to set email alerts
|

Altered Plasma Apolipoprotein Modifications in Patients with Pancreatic Cancer: Protein Characterization and Multi-Institutional Validation

Abstract: BackgroundAmong the more common human malignancies, invasive ductal carcinoma of the pancreas has the worst prognosis. The poor outcome seems to be attributable to difficulty in early detection.MethodsWe compared the plasma protein profiles of 112 pancreatic cancer patients with those of 103 sex- and age-matched healthy controls (Cohort 1) using a newly developed matrix-assisted laser desorption/ionization (oMALDI) QqTOF (quadrupole time-of-flight) mass spectrometry (MS) system.ResultsWe found that hemi-trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 25 publications
3
78
0
Order By: Relevance
“…One reason could be the posttranslational modification of the proteins. Investigations of other groups and our own studies have demonstrated that modifications and truncated forms of proteins such as apolipoproteins and transthyretin may represent disease-specific signatures [17], [41][43]. The modified protein forms are binding with a low affinity, or not at all, to the immobilised antibodies on the depletion columns and, therefore, are not efficiently removed.…”
Section: Discussionmentioning
confidence: 97%
“…One reason could be the posttranslational modification of the proteins. Investigations of other groups and our own studies have demonstrated that modifications and truncated forms of proteins such as apolipoproteins and transthyretin may represent disease-specific signatures [17], [41][43]. The modified protein forms are binding with a low affinity, or not at all, to the immobilised antibodies on the depletion columns and, therefore, are not efficiently removed.…”
Section: Discussionmentioning
confidence: 97%
“…In healthy subjects, 3 basic isoforms are found which we labeled ApoA2‐ATQ/ATQ, ApoA2‐ATQ/AT and ApoA2‐AT/AT), by the lengths of each of the homomers. Patients with PDAC show additional isomers formed through two aberrant processing patterns of ApoA2i: a hyper‐processing pattern of ApoA2i, which leads to predominantly light isoforms such as ApoA2‐AT/AT, ApoA2‐AT/A and ApoA2‐A/A, and a hypo‐processing pattern which leads to a predominance of heavy isoforms such as ApoA2‐ATQ/ATQ . The aberrant processing is likely a consequence of abnormal expression and release of carboxypeptidase A, a digestive enzyme that is primarily synthesized by the pancreas, and leads to a reduction in plasma levels of ApoA2‐ATQ/AT, the major intermediate isoform of ApoA2i, in comparison with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant processing is likely a consequence of abnormal expression and release of carboxypeptidase A, a digestive enzyme that is primarily synthesized by the pancreas, and leads to a reduction in plasma levels of ApoA2‐ATQ/AT, the major intermediate isoform of ApoA2i, in comparison with healthy subjects. Aberrant processing of ApoA2 is observed not only in relation to pancreatic malignancies (including early‐stage cancers), but also in individuals with intraductal papillary mucinous neoplasia (IPMN) and other pancreatic conditions (e.g., chronic pancreatitis) predisposing to pancreatic cancer development …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AUC value of apoA2-ATQ/AT in the German cohort was 0.958, and the diagnostic accuracy to distinguish PDAC from healthy controls was confirmed by the German cohort [35]. …”
Section: Possible Detection Of the Early Stage Of Pancreatic Cancer Andmentioning
confidence: 99%